Current Murine Models and New Developments in H3K27M Diffuse Midline Gliomas - Welby, John P.; Kaptzan, Tatiana; Wohl, Anton; Peterson, Timothy E.; Raghunathan, Aditya; Brown, Desmond A.; Gupta, Shiv K.; Zhang, Liang; Daniels, David J. (Frontiers in Oncology, 2019)
Diffuse Midline Gliomas with Histone 3-Lysine-27-Methionine (H3K27M) mutation constitute the majority of Diffuse Intrinsic Pontine Glioma (DIPG), which is the most aggressive form of pediatric glioma with a dire prognosis. DIPG are lethal tumors found in younger children with a median survival <1 year from diagnosis. Discovery of the characteristic H3K27M mutations offers opportunity and hope for development of targeted therapies for this deadly disease. The H3K27M mutation, likely through epigenetic alterations in specific H3 lysine trimethylation levels and subsequent gene expression, plays a significant role in pathogenesis of DIPG. Animal models accurately depicting molecular characteristics of H3K27M DIPG are important to elucidate underlying pathologic events and for preclinical drug evaluation. Here we review the past and present DIPG models and describe our efforts developing patient derived cell lines and xenografts from pretreated surgical specimens. Pre-treated surgical samples retain the characteristic genomic and phenotypic hallmarks of DIPG and establish orthotopic tumors in the mouse brainstem that recapitulate radiographic and morphological features of the original human DIPG tumor. These models that contain the H3K27M mutation constitute a valuable tool to further study this devastating disease and ultimately may uncover novel therapeutic vulnerabilities.